The complete mitochondrial genome of Holothuria fuscocinerea (Jaeger,1833) - Sun, Yi (Mitochondrial DNA B Resour, 2019)
In this study, the complete mitochondrial genome of Holothuria fuscocinerea was sequenced on an Illumina platform and assembled using NovoPlasty v. 2.7.1. It was submitted to NCBI GenBank and is available with accession number MN542416. The genome was 15,827 bp in size and contains 22 tRNA genes, 12 protein-coding genes, and 2 rRNA genes. The composition of A + T in Holothura spinifera mtDNA was 60.30%. Except ND6 and 5 tRNAs, the others are not on the H-strand. The phylogenetic relationship of 13 species of sea cucumber were analyzed using the neighbor-joining method by software MEGA5.0. Holothuria fuscocinerea was most closely related to Holothuria polii.